Stock Selectivity Skill, Market Timing Ability, Risiko, Size, and Comparison of Performance Islamic Share Mutual Funds - Elliv Hidayatul Lailiyah; Rahmat Setiawan (IQTISHODUNA: Jurnal Ekonomi Islam, 2020)
The Muslim population in Indonesia is one of the highest at around 87%. The high population of the Muslim in Indonesia should be able to provide great potential in terms of Islamic finance as an investment activity, which will certainly contribute positively to the Indonesian economy. Investors will always be interested in investment with high returns and low risk. One of the alternatives is mutual funds, especially sharia equity mutual funds. The choice of the right mutual fund should pay attention to how the performance of the mutual fund. This study examines how the performance of sharia equity mutual funds using the Sharpe, Treynor, and Jensen methods are affected by stock selectivity skills, market timing ability, risk, and size during 2012-2017. The finding of this research is stock selectivity skills, market timing ability, risk, and size are a significantly positive influence on the performance of sharia equity mutual fund. The influence of stock selectivity skill, market timing ability, risk, and size are very strong if measured by the treynor method.